Association Between Acupuncture and Knee Surgery for Osteoarthritis: A Korean, Nationwide, Matched, Retrospective Cohort Study - Gang, Byeong-Gu; Shin, Joon-Shik; Lee, Jinho; Lee, Yoon Jae; Cho, Hyun-Woo; Kim, Me-riong; Kang, Kyungwon; Koh, Wonil; Kim, Eun-Jung; Park, Yeoncheol; Nam, Dongwoo; Ha, In-Hyuk (Frontiers in Medicine, 2020)
Objectives: The present study was undertaken to investigate the relationship between acupuncture therapy and surgery rate. Design: Matched, retrospective cohort study. Materials and Methods: From nationwide health insurance data (2002-2013 cohort data published by the National Health Insurance Service of Korea), patients with new cases of knee osteoarthritis that occurred between January 1, 2004 and December 31, 2010 were analyzed. Patients were divided into an acupuncture group (AG) and a control group (CG), based on records of acupuncture therapy. Propensity scores were calculated by using gender, age, income level, and Charlson comorbidity index (CCI), with the groups matched at a ratio of 1:3 (AG:CG). The final analysis period was 2 years after the first acupuncture therapy for AG and 2 years after initial diagnosis for CG; surgery rates were compared between the two groups. Stratified analyses were performed based on age, gender, and income level; sensitivity analyses were performed based on the frequency and duration of acupuncture therapy. Results: Propensity score-matched AG and CG included 8,605 and 25,815 subjects, respectively. Post-matching surgery rates were 0.26% and 0.93% in AG and CG, respectively. For all age groups, AG showed a lower surgery rate than CG. In the analysis based on gender, the female group showed a significantly lower hazard ratio of 0.225. In analysis based on income level, the results of the entire group were significant, with the lower income group showing the lowest hazard ratio. In sensitivity analyses, AG tended to show a lower surgery rate than CG. Conclusions: The present study demonstrated that acupuncture therapy is associated with a low rate of surgery for knee osteoarthritis. Additional studies are needed to support this conclusion.